What has Athens to Do with Patmos? Rhetorical Criticism of the Revelation of John (1980—2005) - DeSilva, David A. (Currents in biblical research, 2008)
While Revelation does not immediately recommend itself for analysis along the lines of Greek and Latin rhetoric, scholars have made considerable progress analyzing the persuasive strategies of Revelation from this methodological orientation. Energetic attention has been given to John's strategies for establishing authority for his message and deconstructing the authority of rival 'orators'. A number of articles have identified and analyzed implicit and explicit enthymemes in Revelation, the deployment of typical epideictic and deliberative topics, and the contributions of intertexture to rational persuasion. Study of John's style has demonstrated John's finesse and purposefulness in deploying standard figures of thought and diction, while investigation of rhetorical arrangement has generally proceeded in ways that have respected Revelation's complexity and its distance from the standard forms of oratory. Although critics generally affirm the importance of John's appeals to the emotions, this line of investigation has been the least developed.